102 Is the use of sub-cutaneous alfentanil outside the ccu setting compliant with local guidelines? a retrospective audit in a tertiary cancer centre. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Tweddle, A; Most, J; Halley, A; Droney, J
Abstract : Background: The Royal Marsden NHS Foundation Trust is a tertiary referral cancer centre. The Symptom control and palliative care team have opioid prescribing guidelines. There are specific guidelines for Alfentanil given that it is an infrequently prescribed drug on the inpatient wards, to reduce the risk of error. We carried out a retrospective re-audit of our adherence to the trust alfentanil prescribing guidelines. Methods: We identified, using the ward controlled drug log books, all inpatients across the trust (except those on CCU) who had Alfentanil prescribed at any point during 2016. We extracted data on the grade of prescriber, whether the palliative care team were consulted, indication for use, documentation of calculation, the breakthrough dose prescribed and if the calculation had been checked with a senior team member. Results: 59 patients in 2016 had been prescribed alfentanil. In 100% of cases the palliative care team had been consulted. In 59% of cases the prescriber was SHO level. The most common indication was renal impairment. In 99% of cases the indication was appropriate. In only 45% of cases there was documentation of a calculation. 85% of those in whom alfentanil was used as a PRN had an appropriate PRN dose charted. In only 54% of cases there had been discussion with a senior team member. Conclusion: There are improvements we can make in the documentation of the calculation of the alfentanil dose and also in engagement with the need to discuss the dose calculation. We proposed that the ward pharmacists check the dose conversion and verify that there has been discussion with a senior palliative care team member, as part of their routine inpatient drug chart checking process. We also proposed that specific guidance is given on the trust standards for prescribing alfentanil as part of the junior doctor induction programme